Ileocecal Intussusception with Histomorphological Features of Inflammatory Neuropathy in Adenovirus Infection - Elke Kaemmerer; Jens J. W. Tischendorf; Gerd Steinau; Norbert Wagner; Nikolaus Gassler (Gastroenterology Research and Practice)
The pathophysiological mechanisms for ileocecal intussusception in children with adenovirus infection are not well characterized. Here we demonstrate coincidence of adenovirus infection and inflammatory neuropathy of myenteric plexus in two children with ileocecal intussusception. Inflammatory neuropathy, an unspecific morphological feature which is found in peristalsis disorders, was morphologically characterized by the influx of CD3 positive lymphocytes in nervous plexus. To our knowledge, this is the first report suggesting peristalsis disorders from inflammatory neuropathy as additional mechanism in the pathophysiological concept of adenovirus-associated ileocecal intussusception.